The magnetosphere of the close accreting PMS binary V4046 Sgr AB. Issue Volume 9:Issue S302(2013) (7th August 2014) - Gregory, S. G.; Holzwarth, V. R.; Donati, J.-F.; Hussain, G. A. J.; Montmerle, T.; Alecian, E.; Alencar, S. H. P.; Argiroffi, C.; Audard, M.; Bouvier, J.; Damiani, F.; Güdel, M.; et al.
Abstract: We present a preliminary 3D potential field extrapolation model of the joint magnetosphere of the close accreting PMS binary V4046 Sgr. The model is derived from magnetic maps obtained as part of a coordinated optical and X-ray observing program.